Patient Pathway Analysis: A Study on the Utilization of Laboratory and Radiological Tests in Routine Midwifery Intervention - Alharbi, Mohsen Sameer Mohsen; Johali, Mohammed Ahmed Ibrahim; Alhejaili, Jalal Saleem Dakhillah; Jafari, Mohammed Ahmed Farj; Al-Juhani, Nawaf Salah Suwailih; Alshikhi, Ahmed Ali Abdo; Alzahrani, Mohammed Rashed Mohammed; Alsuwaileh, Fatimah Nasser Ali; Alhindi, Shaza Mahmoud; Alsaedi, Jawaher Ahmad Mohammed; Haider, Sawsan Hasan Husein; Alzahrani, Mohammed Ahmed Abduallh (Journal of Ecohumanism, 2025)
Background: Patient Pathway Analysis (PPA) is an increasingly utilized health systems approach that evaluates patient movement across healthcare services and identifies diagnostic and treatment gaps. In maternal and midwifery care, laboratory and radiological investigations constitute essential components of routine intervention, supporting early diagnosis, risk stratification, and maternal–fetal safety. However, inefficiencies in diagnostic utilization, delayed referrals, and variability in practice remain global concerns.Objective: This literature review aims to analyze the patient pathway in routine midwifery care with a focus on the utilization patterns, clinical relevance, timing, accessibility, and health system implications of laboratory and radiological tests.Methods: A structured literature review was conducted using peer-reviewed articles, WHO guidelines, and maternal health policy reports. The review synthesizes evidence on antenatal, intrapartum, and postpartum diagnostic pathways, emphasizing interdisciplinary collaboration among midwives, laboratory professionals, radiologists, and healthcare administrators.Results: Evidence indicates that timely laboratory testing (hemoglobin, blood grouping, infectious screening, glucose tolerance testing) and obstetric ultrasound significantly reduce maternal and neonatal morbidity. However, disparities in access, over-utilization in high-income settings, and under-utilization in low-resource environments remain prevalent. Patient pathway bottlenecks commonly occur at referral, test turnaround time, and result interpretation stages.Conclusion: Optimizing diagnostic utilization within midwifery-led care requires integrated pathway mapping, standardized protocols, digital health integration, and interprofessional coordination. Patient Pathway Analysis offers a systems-level framework for improving maternal health outcomes.